Table_1_Seasonal Hypometabolism in Female Moose.DOCX - Anne Randi Græsli; Alexandra Thiel; Boris Fuchs; Navinder J. Singh; Fredrik Stenbacka; Göran Ericsson; Wiebke Neumann; Jon M. Arnemo; Alina L. Evans (2020)
How animals respond to a changing environment is a key question in ecological research. Animals living at higher latitudes are exposed to pronounced seasonal differences in both climate and in resource availability. Endotherms living in those environments have the ability to maintain a constant high body temperature (T b ), over a wide range of ambient temperatures (T a ). Nonetheless, many endotherms display seasonal shifts in metabolic rate (MR). Here, we studied the annual and circadian cycle of T b and heart rate (HR) in female moose (Alces alces) in relation to activity and T a . HR also can be used as a proxy of MR to calculate energy budgets. We deployed biologgers to 12 free-ranging female moose; a temperature sensor in the rumen, a HR logger subcutaneously, and a GPS collar equipped with acceleration and T a sensors. We documented seasonal differences in T b , HR and activity of moose, with lower levels during winter and higher values during summer. The highest daily mean T b and HR were 38.64°C (10 July) and 71.9 beats per minute (bpm; 26 June), whereas the lowest daily mean T b and HR were 38.03°C (17 March) and 40.5 bpm (6 March). High-resolution T b and activity data allowed us to detect circadian and ultradian rhythmicity throughout the year. Based on previous calibration studies, MR decreased by 60% from the highest to the lowest point. Our results demonstrate hypometabolism including lower T b and HR during winter as a strategy to reduce energy expenditure during periods with colder climate and limited availability of resources.